Estructura molecular y poblacional del ganado criollo Colombiano (GCC) (2001)
ABSTRACT: Colombian criollo cattle includes a group of breeds that have adapted to the environmental conditions of our country for more than 400 years. Therefore, they must have important adaptive characteristics that could be used rationally for animal production programs. Its then necessary to characterize these criollo breeds to determine the degree of genetic variability since it is this parameter which ultimately determines the success or failure of any genetic program directed to preservation and improvement. This paper explores intra and inter genetic variability of each colombian criollo breed and compare it with Brahman. Microsatellite markers were used and three indexes of intrabreed variability were estimate: Endogamy (Fis), Heterocigocity (Ho) and Average number of alleles (NPA). Additionally a tree of genetic distance was created. The indexes of genetic variability found for the 7 breeds were as intermediate, similar to other bovine populations in the world. We will continue increasing the number of loci and individuals per breed, in order to have better estimates of genetic diversity, phylogenetic relationships, and eventual introgression with foreign breeds.